Enhancing Parent–Child Communication and Parental Self-Esteem With a Video-Feedback Intervention: Outcomes With Prelingual Deaf and Hard-of-Hearing Children - Lam-Cassettari, Christa (J Deaf Stud Deaf Educ, 2015)
Evidence on best practice for optimizing communication with prelingual deaf and hard-of-hearing (DHH) children is lacking. This study examined the effect of a family-focused psychosocial video intervention program on parent–child communication in the context of childhood hearing loss. Fourteen hearing parents with a prelingual DHH child (Mage = 2 years 8 months) completed three sessions of video interaction guidance intervention. Families were assessed in spontaneous free play interactions at pre and postintervention using the Emotional Availability (EA) Scales. The Rosenberg Self-esteem Scale was also used to assess parental report of self-esteem. Compared with nontreatment baselines, increases were shown in the EA subscales: parental sensitivity, parental structuring, parental nonhostility, child responsiveness, and child involvement, and in reported self-esteem at postintervention. Video-feedback enhances communication in families with prelingual DHH children and encourages more connected parent–child interaction. The results raise implications regarding the focus of early intervention strategies for prelingual DHH children.